Clearcutting alters decomposition processes and initiates complex restructuring of fungal communities in soil and tree roots - Kohout, Petr; Charvátová, Markéta; Štursová, Martina; Mašínová, Tereza; Tomšovský, Michal; Baldrian, Petr (The ISME journal, 2018)
Forest management practices often severely affect forest ecosystem functioning. Tree removal by clearcutting is one such practice, producing severe impacts due to the total reduction of primary productivity. Here, we assessed changes to fungal community structure and decomposition activity in the soil, roots and rhizosphere of a Picea abies stand for a 2-year period following clearcutting compared to data from before tree harvest. We found that the termination of photosynthate flow through tree roots into soil is associated with profound changes in soil, both in decomposition processes and fungal community composition. The rhizosphere, representing an active compartment of high enzyme activity and high fungal biomass in the living stand, ceases to exist and starts to resemble bulk soil. Decomposing roots appear to separate from bulk soil and develop into hotspots of decomposition and important fungal biomass pools. We found no support for the involvement of ectomycorrhizal fungi in the decomposition of roots, but we found some evidence that root endophytic fungi may have an important role in the early stages of this process. In soil, activity of extracellular enzymes also decreased in the long term following the end of rhizodeposition by tree roots.
Keywords: mykobiom; houby; Biomass; Pinus; Rhizosphere; rhizosféra; Mycobiome; půdní mikrobiologie; mykorhiza; stromy; Fungi; Mycorrhizae; Plant Roots; Soil Microbiology; ekosystém; Ecosystem; Soil; půda; Trees; biomasa; kořeny rostlin; borovice